Association between Taste Sensitivity and Self-Reported and Objective Measures of Salt Intake among Hypertensive and Normotensive Individuals. (23rd October 2012) - Piovesana, Paula de Moura; Sampaio, Karina de Lemos; Gallani, Maria Cecília B. J.
Abstract : This study investigated the gustatory threshold for salt and its relationship with dietary salt intake among hypertensive (n = 54 ) and normotensive (n = 54 ) subjects. Salt intake was evaluated through 24-hour urinary sodium excretion and self-reported measures (discretionary salt, Sodium- Food Frequence Questionnaire (Na-FFQ), and 24-hour recall). Detection and recognition thresholds were higher among hypertensive subjects, as well as the total sodium intake. Detection and recognition thresholds were positively related to discretionary salt and total intake of the group as whole. Hypertensive and normotensive subjects presented positive correlations between taste sensitivity and the different measures of salt intake. To conclude, a positive correlation exists between taste threshold and salt intake and both seem to be higher among hypertensive subjects. The combined use of methods of self-report and assessment of taste thresholds can be useful in health promotion and rehabilitation programs, by screening subjects at higher risk of elevated salt intake and the critical dietary behaviors to be targeted as well to evaluate the result of targeted interventions.